Assessment of physical activity among adolescents: a guide to the literature - Sedlačík, Marek; Lacinová, Veronika; Hasilová, Kamila (Frontiers in Psychology, 2023)
The aim of this article is to systematically review articles and annual reports concerning young peoples' physical activity (PA) and linking this to considerations of the state and national defence.A systematic search of the literature included an analysis of publications accessible in global databases and other available books, student papers and projects. The articles and reports were categorized based on year of publication, methods used, age of respondents, sample size, country, and digital object identifier (DOI).The result of this search is an overview of the extent and manner in which the worldwide scientific community is addressing the current situation and the long-term development of the physical fitness of adolescents. This publication also maps to what extent professional publications and articles are addressing PA from the perspective of the needs of armies and armed forces of various countries around the world.The article provides a systematic overview of methods used to measure PA, and an overview of articles dealing with assessing PA. The examined articles indicate that from the perspective of not only national defence, but also health and overall quality of life, in particular, we need initiatives to encourage and motivate young people to increase their everyday PA. The research therefore also includes an overview of factors that may considerably influence PA. The results ascertained in this publication will be used, i.a. for investigating a longitudinal defence research project of the Ministry of Defence of the Czech Republic in which the authors are participating.